Biomechanical Analysis about Syndesmotic Stability for AITFL Augmentation with Fibular Plate - Katsunori Takahashi MD; Atsushi Teramoto; Yasutaka Murahashi MD, PhD; Kota Watanabe; Toshihiko Yamashita Md, PhD (Foot & Ankle Orthopaedics, 2023)
Category: Trauma; Sports Introduction/Purpose: Surgical technique to treatment syndesmosis injury is controversial. Additional suture-tape (ST) augmentation of anterior inferior tibiofibular ligament (AITFL) has been reported to improve syndesmotic stability compared with only suture-button (SB) fixation. ST fixation on the fibula is mainly performed with suture anchors, but suture holes with fibular plates can also be used. However, there is no biomechanical study about syndesmotic injury treated with ST augmentation using fibular plate. The aim of this study is to evaluate the stability of the syndesmosis injury model treated with ST augmentation using fibular plate. Our hypothesis is that ST augmentation using fibular plate can provide equivalent syndesmotic stability compared with ST augmentation using suture anchor. Methods: 8 normal fresh-frozen cadaver legs (4 males and 4 females) were used. The mean age at the time of death was 84.3 (70- 101). The specimens were tested while applied traction and rotational forces to represent dorsiflexion and external rotation of ankle joint. The fibular rotational angle related to the tibia (FRA) and anterior tibiofibular diastasis(aTFD) were measured using the magnetic tracking system while each load was applied. Intact, injured, SB + ST augmentation using suture anchor (anchor model), SB + ST augmentation fixation using fibular plate (plate model) models made, and loaded forces and measured FRA and aTFD with each model. One-way ANOVA was used to evaluate the relationship of the angles or the diastasis among each model. Post-hoc analysis for differences among the models were checked using Dunnett’s test. P value of 0.05 was chosen as the level of significance. Results: With dorsiflexion forces, in the injured model, both FRA and aTFD were significantly increased compared with intact model. In the anchor and plate model, both FRA and aTFD were not significantly different compared with intact model. With external rotation forces, in the injured model, both FRA and aTFD were significantly increased compared with intact model. In the anchor and plate model, both FRA and aTFD were not significantly different compared with intact model. Conclusion: The result of this study presented that ST augmentation using fibular plate provide syndesmotic stability similarly with ST augmentation using suture anchor. This technique was considered to be useful in cases of syndesmosis injury with lateral malleolar fracture. Particularly, it is difficult to use suture anchor for ST fixation to the fibula when there is a comminuted fracture near the AITFL attachment of the fibula. Using plate allows for stable ST fixation to the fibula without worrying about it.